Permeability of the Mercia Mudstone: suitability as caprock to carbon capture and storage sites. Issue 1 (21st March 2015) - Armitage, P. J.; Worden, R. H.; Faulkner, D. R.; Butcher, A. R.; Espie, A. A.
Abstract: The Upper Triassic Mercia Mudstone is the caprock to potential carbon capture and storage (CCS) sites in porous and permeable Lower Triassic Sherwood Sandstone reservoirs and aquifers in the UK (primarily offshore). This study presents direct measurements of vertical ( k v ) and horizontal ( k h ) permeability of core samples from the Mercia Mudstone across a range of effective stress conditions to test their caprock quality and to assess how they will respond to changing effective stress conditions that may occur during CO2 injection and storage. The Mercia samples analysed were either clay‐rich (muddy) siltstones or relatively clean siltstones cemented by carbonate and gypsum. Porosity is fairly uniform (between 7.4 and 10.7%). Porosity is low either due to abundant depositional illite or abundant diagenetic carbonate and gypsum cements. Permeability values are as low as 10 −20  m 2 (10nD), and therefore, the Mercia has high sealing capacity. These rocks have similar horizontal and vertical permeabilities with the highest k h / k v ratio of 2.03 but an upscaled k h / k v ratio is 39, using the arithmetic mean of k h and the harmonic mean of k v . Permeability is inversely related to the illite clay content; the most clay‐rich (illite‐rich) samples represent very good caprock quality; the cleaner Mercia Mudstone samples, with pore‐filling carbonate and gypsum cements, represent fair to good caprock quality. Pressure sensitivity of permeability increases with increasing clay mineral content. As pore pressure increases during CO2 injection, the permeability of the most clay‐rich rocks will increase more than carbonate‐ and gypsum‐rich rocks, thus decreasing permeability heterogeneity. The best quality Mercia Mudstone caprock is probably not geochemically sensitive to CO2 injection as illite, the cause of the lowest permeability, is relatively stable in the presence of CO2 –water mixtures.